Multiple Molecular Pathways in Melanomagenesis: Characterization of Therapeutic Targets - Palmieri, Giuseppe; Ombra, MariaNeve; Colombino, Maria; Casula, Milena; Sini, MariaCristina; Manca, Antonella; Paliogiannis, Panagiotis; Ascierto, Paolo Antonio; Cossu, Antonio (Frontiers in Oncology, 2015)
Molecular mechanisms involved in pathogenesis of malignant melanoma have been widely studied and novel therapeutic treatments developed in recent past years. Molecular targets for therapy have mostly been recognized in the RAS-RAF-MEK-ERK and PI3K-AKT signaling pathways; small-molecule inhibitors were drawn to specifically target key kinases. Unfortunately, these inhibitors may display intrinsic or acquired resistance and various evidences suggest that targeting a single component in pathogenetic signaling pathways could not yield significant anti-tumor responses. Therefore, knowledge of the multiple altered signaling events involved in response and resistance to targeted treatments will allow to speed up the development of more effective combination therapies. In this review, we summarize the known molecular mechanisms underlying either intrinsic and acquired drug resistance either alternative roads to melanoma pathogenesis, which may become targets for innovative anticancer approaches.